Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1177/0011128792038004002
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Drug Use and Criminal Behavior: Results from the National Household Survey on Drug Abuse

Abstract: In 1991, questions on involvement in criminal behavior and being arrested and booked for a crime were added to the National Household Survey on Drug Abuse (NHSDA) to ascertain the relationship between drug use and criminal behavior. Analysis shows that drug use is a strong correlate of being booked for a criminal offense, but age is the more important correlate of criminal involvement. There were few differences in models predicting violent as opposed to property crime, although minority status was a more impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 15 publications
4
57
1
1
Order By: Relevance
“…However, the majority of cocaine users, 58.8% and the majority of methamphetamine users 60% did not report committing a property crime within the past 12 months. The results regarding cocaine use were significant and are supported by the literature previously discussed (Nurco et al, 1989, Harrison & Gfroerer, 1992 Gerkin's (2009) study, which found that the second largest category of responses for arrest charges was property crimes among methamphetamine users. Methamphetamine users who were arrested were more likely to be arrested for drug possession or property crime than for violent crime (Gizzi & Gerkin, 2009).…”
Section: Control Variablessupporting
confidence: 81%
See 2 more Smart Citations
“…However, the majority of cocaine users, 58.8% and the majority of methamphetamine users 60% did not report committing a property crime within the past 12 months. The results regarding cocaine use were significant and are supported by the literature previously discussed (Nurco et al, 1989, Harrison & Gfroerer, 1992 Gerkin's (2009) study, which found that the second largest category of responses for arrest charges was property crimes among methamphetamine users. Methamphetamine users who were arrested were more likely to be arrested for drug possession or property crime than for violent crime (Gizzi & Gerkin, 2009).…”
Section: Control Variablessupporting
confidence: 81%
“…The crime of selling drugs is the primary criminal activity among drug users (Harrison & Gfroerer, 1992). Gizz and Gerkin (2009) were possession charges.…”
Section: Methamphetamine Use and Drug Salesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although there is no universally accepted categorization of these patterns or pathways, the following generalizations about drug use and adolescent development are generally recognized: ◆ Substance use commonly follows a sequence from tobacco and alcohol to cannabis and then to more dangerous substances (Newcomb and Bentler, 1990;Rutter, 1996;Kandel, 1984a, 1984b). ◆ Beginning substance use and abuse in early adolescence is associated with: ❖ More serious delinquency and longer deviant careers (Moffitt, 1993a;Craddock, Collins, and Timrots, 1994;Harrison and Gfroerer, 1992;Brook et al, 1996;Loeber, StouthamerLoeber, and White, 1999). ❖ Antisocial personality disorders in later life (Myers, Stewart, and Brown, 1998;van den Bree, Svikis, and Pickens, 2000).…”
Section: Background: Substance Use In Adolescent Developmentmentioning
confidence: 99%
“…For this reason, large national studies rely on self-report data to generate prevalence rates of substance use (Craddock, Collins, and Timrots, 1994;Harrison and Gfroerer, 1992;Golub et al, 2002; U.S. Department of Health and Human Services, 1996). For self-report data to be valid, subjects must understand the questions, accurately recall the information requested, and disclose information honestly (Lessler and O'Reilly, 1997;Turner et al, 1998;Wasserman et al, 2002;Catania et al, 1990;Huang, Watters, and Case, 1988;Miller, 1997).…”
Section: Self-reportmentioning
confidence: 99%